APPLICATION OF JIGSAW-TYPE COOPERATIVE LEARNING MODEL TO IMPROVE LEARNING OUTCOMES - Anggrainy, Rani; Tresdiawan, Rendi Ardi; Mubarak, Ibnu; Sutia, Iyep; Lubi, Ahmad (Universitas Pendidikan Indonesia, 2022)
This study aims to (1) find out the difference in improving student learning outcomes between those who use the jigsaw-type cooperative model and students who use the lecture model, and (2) find out the increase in student learning outcomes after applying the cooperative learning model with jigsaw type. Metode penelitian yang digunakan adalah metode eksperimental. The experimental method is used to look for a causal relationship between two factors that the researcher deliberately caused. The population in this study was all Class XI students majoring in Motorcycle Business Engineering at one of the State Vocational Schools in Bandung totaling 5 classes. The research samples were taken in two classes, namely one experimental class and one control class, the sampling technique was carried out random sampling cluster. The instruments used are test instruments and obsrvation sheets. The results showed that there was a significant difference between the learning outcomes of students who used a jigsaw-type cooperative model and students who got learning with a lecture model. The average final score of learners using the jigsaw-type cooperative model was higher than those using lectures. The N-Gain value index of the jigsaw type cooperative model category is quite effective and the lecture model of its N-Gain index category is ineffective.Keywords: Learning Model; cooperative; jigsaw; Experimental; N-Gain